Nonlinear optical properties of nanoparticles prepared via pulsed laser ablation - Savelyev, Egor S.; Lapin, Ivan N.; Fakhrutdinova, Elena D.; Svetlichnyi, Valerii A. (Proceedings of SPIE)
This paper studies nonlinear optical properties of colloidal solutions obtained via pulsed laser ablation (PLA) of bulk targets of magnesium (Mg), bismuth (Bi), tin (Sn), and antimony (Sb) in water and ethanol. In this research Nd:YAG laser (1064 nm, 180 mJ, 7 ns, 20 Hz) was used as a radiation source. Nonlinear absorption and scattering of colloidal solutions were studied by direct nonlinear transmission (NLT) with power density in the range of 1-450 MW/cm2. Except for the solution obtained through the ablation of magnesium in water, all the samples exhibit a nonlinear decrease of transmission as a consequence of the increase of pumping power density. Along with this, the effect of nonlinear limitation of laser radiation depends on the type of particles and solvents.